2014
DOI: 10.1155/2014/612838
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Anatomy and Kinematics in Asian and Caucasian TKA Patients: Influence on Implant Positioning and Subsequent Loading Conditions in Mobile Bearing Knees

Abstract: The objective of our study was to determine the mechanical stress conditions under tibiofemoral loading with an overlay of knee kinematics in deep flexion on two different mobile bearing designs in comparison to in vivo failure modes. This study investigates the seldom but severe complication of fatigue failure of polyethylene components at mobile bearing total knee arthroplasty designs. Assuming a combination of a floor-based lifestyle and tibial malrotation as a possible reason for a higher failure rate in A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…In the absence of database for Asian population, most surgeons have to rely on the data obtained from different ethnic groups both for the diagnosis and treatment. It is, however, clear that Asian knees differ from those of their Western counterpart2224). Table 6 shows the comparison of values of various parameters between the established literature based on Western population and the current study8,12,13,2530).…”
Section: Discussionmentioning
confidence: 74%
“…In the absence of database for Asian population, most surgeons have to rely on the data obtained from different ethnic groups both for the diagnosis and treatment. It is, however, clear that Asian knees differ from those of their Western counterpart2224). Table 6 shows the comparison of values of various parameters between the established literature based on Western population and the current study8,12,13,2530).…”
Section: Discussionmentioning
confidence: 74%
“…Other authors reported revision rates related to implant failure in range from 0,073 to 0.94% [7,15,18].…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of musculoskeletal joint kinematics and function ( 32 , 40 , 41 ) applying latest-stage in silico analysis methods like dynamic patient activity-based FEA simulation ( 42 ) and musculoskeletal modelling. Furthermore, augmented reality applications, artificial intelligence algorithms, and widespread retrospective clinical data files, allows for a better understanding of the expected success of an intended treatment or procedure for different patient phenotypes (cluster).…”
Section: How To Define the New Implant Or The Implant-related Instrum...mentioning
confidence: 99%